Analisis Struktur Sosial Ibu Rumah Tangga Dalam Strategi Peningkatan Kesejahteraan Keluarga - Sukoco, Dear; Hidayat, Fahmi; Wardhana, Wisnu (Universitas Terbuka, 2023)
Abstract: The plantation sector has experienced good growth in terms of production, investment, exports, and so on, so that it has a large role for the Indonesian economy. It can not be separated from the work of its employees. At PTPN XII Kalitelepak Glenmore Plantation, there are many labor employees who work and live in the plantation area. Of the many labor employees who work on the Kalitelepak plantation, not a few women also work as sugar cane workers. A group of women who live in Afdeling Sumber Tempur include housewives who work to fulfill their family’s economy. The role of women in family life is dominant, they not only play the role of being the housekeeper and all activities in it, but also play the role of breadwinner for the family. The purpose of this research is to describe the role of women as housewives in supporting family welfare through improving the household economy. The method used is descriptive qualitative using a realist ethnographic approach, and is located in the Sumber Tempur Afdeling, Kalitelepak Hamlet, Tulungrejo Village, Glenmore district, Banyuwangi regency. Meanwhile, the informans in this study were a group of housewives who worked as garden laborers in Kalitelepak. Data collection was carried out by interview, observation, and documentation methods. The results of the study show that housewives decided to keep working not only to help their husbands increase income for housing on the plantation. Thus, causing them inevitably to carry out activities as garden laborers.